Do mercado velho à nova feira: a reestruturação da feira do bairro da prata, Campina Grande – PB - Lima , Jéssica Camêlo de Lima (2015)
This current dissertation aimed to analyze the spatial restructuring process carried out in the Feira da Prata, located in the Prata’s neighborhood in the city of Campina Grande, including the time frame between 2005 and 2015. In that sense, we seek to understand how being processed the public policies directed to this fair in order to suit their physical structure, as well as its form of organization to current consumer demands and marketing standards imposed by modern society. In addition, we try to understand how fair dealers take ownership and are organized within the trade fair space, before and after the restructuring process, to make their sociability practices, market their products and establish their working relationships, realizing the contrasts and conflicts arising from the production of a "mental space", the space of the philosophers and urban planners, as opposed to "real space", the physical and social spheres built by fair dealers based on their "knowing/doing” everyday and, at this juncture, infer the “tactics” adopted by fair dealers to establish in this “mental space”. Still we try to investigate what the intentions underlying the government's actions with respect to continuity of policies aimed at fairs, most often, it is linked to the need for self-promotion policy certain hegemonic groups and not necessarily in understanding the historical character, traditional and unique present in these institutions. Regarding the methodological procedures, the research was characterized, above all, in the fieldwork, with interviews application, combined with the theoretical discussion, with the authors assumptions, mainly from the fields of Geography and History, since fairs study requires an interdisciplinary look. Thereby from our investigation and reflections inferred therefore, the restructuring, the manner in which it was achieved, configured as the imposition of an external rationality to the rationality of the fair, having a primary purpose the promotion of political groups in municipal and state levels and no improvement in their working conditions of the fair dealers.